Characterization of terahertz quantum cascade lasers - Tan, Kai Wee (Nanyang Technological University, 2024)
The THz gap has been a concern for researchers since the discovery of the practical usage of THz radiation. The non-invasive and non-damaging properties of this radiation opens up many possible applications such as imaging and gas sensing. In 1994, Quantum Cascade Lasers (QCL) were first demonstrated. Development and improvement of QCL were followed closely after the demonstration, to the point where it was able to generate THz radiation steadily. However, the THz QCL faces limitations such as its low operating temperature and narrow tuning range, restricting it from a wide range of applications. To overcome its limitations, extensive research on the QCL properties has to be conducted. Through the characterization of THz QCL, information of the unique features of each laser can be attained, allowing us to better study and understand it. With ample information on the physical and electrical properties of each laser, we will be able to steer any research in the right direction, including increasing efficiency, reducing limitations, or even bringing in new applications.